The Predictive Value of Pan-Immune-Inflammation Value for Saphenous Vein Graft Disease in Post-Coronary Artery Bypass Grafting Patients - Faruk Serhatlioglu; Zeki Cetinkaya; Yucel Yilmaz (Journal of Cardiovascular Development and Disease)
Background: Coronary artery bypass grafting (CABG) remains the gold standard treatment for patients with significant coronary artery disease (CAD) and high-risk profiles for percutaneous coronary intervention. Despite the frequent use of saphenous vein grafts (SVGs) in CABG, their patency rates are lower than those of arterial grafts. Identifying noninvasive methods to determine SVG patency is crucial. Aims: This study investigates the relationship between a novel inflammation marker, pan-immune-inflammation value (PIV), and SVG patency in post-CABG patients. Methods: The study included 507 patients who underwent coronary angiography (CAG) due to clinical indications between 2016 and 2023. Patients who had undergone CABG at least one year prior with at least one SGV used were divided into two groups based on the presence or absence of SVG stenosis (SGVS). Results: Among the 507 patients, 244 had SVGS. Patients with SVGS exhibited higher levels of diabetes mellitus and inflammatory markers such as NLR, SII, CAR, and PIV. Multivariate analysis identified PIV as an independent predictor of SVGS. ROC analysis showed that a PIV cut-off value > 315.5 predicted SVGS with 75.8% sensitivity and 68.6% specificity. Conclusions: PIV, a simple and easily measurable marker, demonstrated strong predictive value for SVGS in post-CABG patients.